Synthesis and reactions of alkenyl-gem-dichlorocyclopropanes obtained from piperylene - A. I. Musin; Yu. G. Borisova; G. Z. Raskil’dina; R. U. Rabaev; R. R. Daminev; S. S. Zlotskii (Тонкие химические технологии)
Objectives. This study aims to obtain alkenyl-gem-dichlorocyclopropanes from piperylene. The products are then subjected to thermocatalytic isomerization and hydrogenation.Methods. To determine the qualitative and quantitative composition of the reaction crudes, the following analytical methods were used: gas-liquid chromatography using the Crystal 2000 hardware complex, mass spectrometry using a Chromatec-Crystal 5000M device with the NIST 2012 database, and nuclear magnetic resonance (NMR) spectroscopy using a Bruker AM-500 device at operating frequencies of 500 and 125 MHz.Results. Alkenyl-gem-dichlorocyclopropanes were synthesized in the presence of triethylbenzyl ammonium chloride as catalyst. Their isomerization and hydrogenation gave the corresponding gem-dichlorocyclopentene and isomers of alkyl-gem-dichlorocyclopropanes. The structure of synthesized substances were analyzed by gas-liquid chromatography, mass spectrometry, and NMR spectroscopy.Conclusions. The results show that formation of four isomeric substituted gem-dichlorocyclopropanes occurs in high yield during incomplete dichlorocyclopropanation of piperylene. The thermocatalytic isomerization of substituted gem-dichlorocyclopropanes in the presence of SAPO-34 zeolite leads to the formation of one product, i.e., gem-dichlorocyclopentene, and hydrogenation of substituted gem-dichlorocyclopropanes in the presence of Pd/C catalyst gives three isomeric alkyl-gem-dichlorocyclopropanes.